2020
DOI: 10.1021/acs.energyfuels.0c01599
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Pore-Scale Mechanism of Low Salinity Water Injection and the Improvements on Oil Recovery

Abstract: The long-held industry view that the Low Salinity Effect (LSE) depends mainly on rock−fluid interactions has led to failures and successes that can be explained by fluid−fluid interactions. Therefore, elevating our knowledge about the microscopic interactions occurring in the crude oil/brine/rock system appears to be of paramount importance. This paper chooses to outline various analytical tools in combination with a microfluidic instrument (Micromodel) to identify these interactions at simulated reservoir con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…50−53 It was observed during LSWI that polar species of crude oil such as asphaltenes and naphthenic acids can promote the formation of microdispersion leading to wettability alteration accordingly. 9,43,44,54,55 Therefore, studying the oil/water interface of crude oil samples with different physicochemical properties and improving our knowledge about the main responsible surface-active materials at the interface are extremely important.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50−53 It was observed during LSWI that polar species of crude oil such as asphaltenes and naphthenic acids can promote the formation of microdispersion leading to wettability alteration accordingly. 9,43,44,54,55 Therefore, studying the oil/water interface of crude oil samples with different physicochemical properties and improving our knowledge about the main responsible surface-active materials at the interface are extremely important.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The studies conducted by Sanyal et al , showed that the polar species of crude oil (asphaltenes molecules with various polycyclic aromatic rings) and the ions in injection water would influence the performance of LSWI. However, the LSE on the oil recovery has been shown not only for rocks composing of other clay minerals (i.e., chlorite, illite, and muscovite) but also for sandstone rocks free of clay minerals. It was observed during LSWI that polar species of crude oil such as asphaltenes and naphthenic acids can promote the formation of microdispersion leading to wettability alteration accordingly. ,,,, Therefore, studying the oil/water interface of crude oil samples with different physicochemical properties and improving our knowledge about the main responsible surface-active materials at the interface are extremely important.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the interfacial properties of crude oil have received significant attention over the past decades because of their relevance to oil recovery, transport, and processing. For example, most oil extraction processes are based on injecting water-based liquids, called brines, into the porous oil reservoir. The efficiency of this process, known as waterflooding, is generally understood as an interplay between viscous and interfacial forces, and it has been shown that it can be enhanced by tuning the chemical composition of the brine, for example, by reducing its salinity or by selectively increasing the concentration of certain divalent ionic species. However, despite intense research in this field, the underlying mechanisms that lead to improved oil recovery are still debated. Moreover, the complex rheology of the interfacial films dictates the stability of oil/water emulsions, with implications in oil transport, processing, and final quality. , …”
Section: Introductionmentioning
confidence: 91%
“…They found out that water-in-oil dispersions led to oil swelling and wettability alteration. They concluded that crude oils’ tendency to form microdispersions could be an essential screening method for oil reservoirs before waterflooding . The swelling of the oil droplets during LSW injection has been confirmed by some other reserachers .…”
Section: Introductionmentioning
confidence: 99%